2023
DOI: 10.1002/mp.16876
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic modeling and parametric imaging of 18F‐PSMA‐11: An evaluation based on total‐body dynamic positron emission tomography scans

Hui Yuan,
Guojin Zhang,
Taotao Sun
et al.

Abstract: BackgroundThe prostate‐specific membrane antigen (PSMA) targeted positron‐emitting tomography (PET) tracers are increasingly used in clinical practice, with novel tracers constantly being developed. Recently, 18F‐PSMA‐11 has been gaining growing interest for several merits; however, direct in vivo visualization of its kinetic features in humans remains lacking.PurposeTo visualize the kinetic features of 18F‐PSMA‐11 in healthy subjects and patients with prostate cancer derived from the total‐body dynamic PET sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 51 publications
0
0
0
Order By: Relevance
“…Non-FDG tracers have been used for parametric imaging with TB-PET [48][49][50][51]. Chen et al found that the kinetics of 68 Ga-PSMA-11 in patients with prostate cancer is well described by the irreversible two-tissue compartment model (2T3k) model, and the quality of parametric imaging, namely high sensitivity and low noise, meets clinical diagnostic needs [52].…”
Section: Parametric Imagingmentioning
confidence: 99%
“…Non-FDG tracers have been used for parametric imaging with TB-PET [48][49][50][51]. Chen et al found that the kinetics of 68 Ga-PSMA-11 in patients with prostate cancer is well described by the irreversible two-tissue compartment model (2T3k) model, and the quality of parametric imaging, namely high sensitivity and low noise, meets clinical diagnostic needs [52].…”
Section: Parametric Imagingmentioning
confidence: 99%